PENGARUH ROA, ROE DAN NPM TERHADAP HARGA SAHAM (STUDI PADA PERUSAHAAN PERBANKAN YANG TERDAFTAR DI BEI PADA MASA PENDEMI COVID 19 PERIODE 2019-2021) - Affan, Junaidi; Nuswantoro, Bakti Aguling (LPPM Akademi Manajemen Administrasi Yogyakarta, 2023)
The purpose of this study is to determine the effect of return on assets (ROA), return on equity (ROE), net profit margin (NPM) and on banking stock prices in Indonesia during 2019-2021. The population in this study are 33 banking companies listed on the Indonesia Stock Exchange (IDX) for 2019-2021. The sampling technique uses saturated sampling techniques so that 33 banking companies are obtained. The research method used in this study is a quantitative research method. Data analysis techniques were carried out using classical assumption tests which included normality tests, multicollinearity tests, heteroscedasticity tests and autocorrelation tests. While hypothesis testing is done by multiple regression analysis. The results of this study indicate that the ROA variable has a partial effect on stock prices as evidenced by a significant value of 0.013 <0.05. For the ROE variable, it has no partial effect on stock prices as evidenced by a significant value of 0.860 > 0.05. While the NPM variable has no partial effect on stock prices, it is proven that the significant value is 0.350 > 0.05. For the independent variables Return On Assets (ROA), Return On Equity (ROE) and Net Profit Margin (NPM) affect the dependent variable on stock prices by 9.9%. Simultaneously all ROA, ROE and NPM variables have a significant effect on stock prices.